Urinary Tract Infections in Kidney Transplant Patients: An Open Challenge—Update on Epidemiology, Risk Factors and Management - Biagio Pinchera; Emilia Trucillo; Alessia D’Agostino; Ivan Gentile (Microorganisms)
Urinary tract infections are one of the main complications in kidney transplant patients, with a significant impact on graft function and survival. In fact, it is estimated that up to 74% of kidney transplant patients experience at least one episode of UTIs in the first year after transplantation, with an increased risk of graft loss and an increased risk of mortality. Several risk factors have been identified, such as female gender, old age, diabetes mellitus, immunosuppression, pre-transplant UTIs, urinary tract abnormalities, and prolonged dialysis. The worsening burden of antimicrobial resistance is also in itself a risk factor and a major complication in evolution and management. The management of prophylaxis, asymptomatic bacteriuria, and UTIs is still an open challenge, with some points to be clarified. Faced with such scenarios, our review aimed to evaluate the current epidemiology, examine the risk factors, and consider all the possibilities and methods of management, giving a current view and evaluation of the topic.